ANALISIS APLIKASI 5C (CHARACTER, CAPACITY, CAPITAL, CONDITIONAL, AND COLLATERAL) PADA PEMBIAYAAN MURABAHAH DI BMT MANDIRI UKHUWAH PERSADA - Qomariyah Qomariyah (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2015)
This research aims to answer questions about how the application of the existing 5C in BMT Ukhuwah Persada Mandiri–particularly for customer of murabaha financing–in determining a client's deserve murabaha financing. This research is a qualitative research. Research data gathered from the interview directly with 17 customers, AO and Manager of BMT Mandiri Ukhuwah Persada in Kedinding Lor gang Tanjung Surabaya. This research analyzed using descriptive analysis method. The results of this research show that the financing customer in BMT Ukhuwah Persada Mandiri Surabaya feel particularly liked doing the murabaha financing because the process is quick and easy. It makes the customer has in good faith to make installment payments in accordance with a defined period of time.